4CPS-037 The impact of multidisciplinary collaboration in optimising the prescription of antibiotics in a paediatric hospital. (March 2019) - Attjioui, H; Cheikh, A; Lazrak, M; Hamdaoui, O; Aliat, Z; Yaniss, S; Benomar, A; Mefetah, H; Bouatia, M
Abstract : Background: The safe prescription of antibiotics and their rational use constitute an essential link in the management of patients, in which all care actors have an important role. Purpose: To analyse the evolution of antibiotic consumption in a paediatric health establishment, and to develop strategies for optimising the prescription and rationalisation of their use. Material and methods: The analysis concerned four critical antibiotics (ceftazidime, imipenem/cilastine, vancomycin and amikacin), used in six departments of the paediatric hospital over the period from July 2016 to December 2017. The use of antibiotics was evaluated using the defined adult daily doses as a measurement standard that converts the physical quantities of drugs into a standard unit of measurement. In order to overcome the problem of overconsumption, we have put, in collaboration with the health facility's drug committee, some strategies for optimising the prescription of antibiotics, such as the requirement of antibiogram results for prescriptions containing a critical antibiotic, discussion of the choice of antibiotic therapy to limit bacterial resistance and reinforcement of hygiene measures to reduce the incidence of nosocomial infections. Results: The results of the evolution of consumption are presented in the following table 1 in (%): Conclusion: The optimisation of antibiotic use through collaboration and multidisciplinary actions was observed in the results, with considerable variation across services. The success of antibiotic prescribing strategies involves close collaboration between the resuscitator, the infectious disease specialist and the hospital pharmacist. Several studies highlight the value of such collaboration. The effectiveness of this collaboration is, however, conditioned by health professionals developing their knowledge of the particularly complex and specific environment of infections. References and/or acknowledgements: Clinical and economic impact of an antibiotics stewardship programme in a regional hospital in Hong Kong. No conflict of interest.